"The System Had Choked Me Too": Abused Mothers' Perceptions of the Custody Determination Process That Resulted in Negative Custody Outcomes. Issue 9 (May 2021) - Khaw, Lyndal; Bermea, Autumn M.; Hardesty, Jennifer L.; Saunders, Daniel; Whittaker, Angela M.
Intimate partner violence (IPV) is a public health problem that continues to affect abused mothers after separation from an abusive partner. In addition to the risk of ongoing control and violence by abusers, the custody determination process may present challenges for mothers who end up with negative custody outcomes (e.g., share custody with abusers or lose custody). Using constructivist grounded theory techniques, we conducted a qualitative analysis of interviews with 24 abused mothers with negative custody outcomes to understand how they perceive and make sense of the process as a whole, and how they cope with these outcomes. The custody determination process was reportedly complex and stressful, and most mothers did not anticipate a negative custody outcome. Mothers' perceptions and experiences followed three phases: " trusting "the system" to protect them and their children, adapting to "the system" in search of positive outcomes, and, once custody decisions were determined, coping with the aftermath of the judicial system process, either by accepting or resisting the outcome. This study echoes previous calls for further training and policies that make the custody determination process less burdensome and harmful for survivors and their children.